Strengthening Village Identity Through Digital Branding on Websites and Social Media - Ghina Nabilah Effendi; Aliyah B; Diky Chairul Majid; Eka Ariyani Safitri; Muhammad Jihad Alfarizi; Riry Rojaa Sati; Al Fauzi Rahmat (Bakti Cendana, 2026)
Excellent public service is a mandate of the Village Law No. 6 of 2014 to accelerate the achievement of general welfare in village communities. Standards of superior service that are transparent, accountable, effective, and efficient can be realized through the utilization of applications and information and communication technology (ICT), commonly referred to as e-government. The digital village program is one initiative to implement village information systems. This community service activity applied a Participatory Action Research (PAR) approach, fostering collaboration and enhancing stakeholders’ understanding of the importance of digital villages. The program was conducted by lecturers from UIN Sultan Thaha Saifuddin Jambi under the Kukerta Mandiri MBKM–Internship–Lecturer Community Service Conversion program, focusing on “Digital Village” in Simpang Sungai Duren Village, Jaluko District, Muaro Jambi Regency. As an initial implementation step, villages were assisted in activating and managing official websites with the desa.id domain, as well as Instagram, Facebook, and YouTube accounts as channels for information and village profile video updates, serving as digital-based information and service media. The results indicate that, despite existing limitations, the potential for villages to evolve into digital villages remains vast and can be further developed toward greater progress.